The darkness within us eaudiobook - Levenseller, Tricia (The Shadows Between Us, 2024)
"Few audiobooks warrant turning off all distractions, closing one's eyes, and simply listening to the story unfold. Narrator Caitlin Davies creates just that experience as she passionately guides listeners through this gripping story of ambition, love, and desire." — AudioFile on The Shadows Between Us The Darkness Within Us is a wickedly delightful companion novel to Tricia Levenseller's The Shadows Between Us. Chrysantha Stathos has won. By hiding her intelligence and ambition behind the mask of a beautiful air-headed girl, she has become a wealthy duchess. And, once her elderly husband dies, she will have all the freedom, money, and safety she's ever wanted. Or so she thought. A man claiming to be the estranged grandson of Chrysantha's lecherous late husband has turned up to steal her inheritance. To make matters worse, her little sister is going to be queen and is rubbing it in her face. Chrysantha decides that the only thing to do is upstage Alessandra at her own wedding. And as for this grandson, he has to go. Never mind that he's extremely handsome and secretive with mysterious powers . . . No, Chrysantha wants Eryx Demos dead, and in the end, a Stathos girl always gets what she wants. A Macmillan Audio production from Feiwel & Friends.